Down Regulation of EGF and AZGP1 Were Associated with Clinical Characteristics in Chronic Rhinosinusitis with Nasal Polyps: An Observation Study - Jin P; Zhang Q; Zang Y; Zhao L; Zhang H; Yu K; Liang X; Zi X; Shi L (Dove Medical Press, 2023)
Peng Jin,* Qinqin Zhang,* Yiran Zang, Li Zhao, Hongyang Zhang, Kena Yu, Xu Liang, Xiaoxue Zi, Li Shi Department of Otolaryngology, The Second Hospital of Shandong University, Jinan, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaoxue Zi, Department of Otolaryngology, The Second Hospital of Shandong University, No. 247, Beiyuan Road, Jinan, Shandong Province, 250033, People's Republic of China, Tel +86 531 85875226, Email zxx201313669@126.comObjective: The mechanisms underlying the chronic rhinosinusitis with nasal polyps (CRSwNP) remained unclear. This study aimed to identify differentially expressed genes (DEGs) in nasal polyps from CRSwNP patients compared to healthy controls and explore key genes and pathways associated with CRSwNP pathophysiology and prognosis.Methods: Three datasets were obtained from the Gene Expression Omnibus database and the intersecting DEGs were identified in CRSwNP patients. Gene Ontology (GO) and protein-protein interaction (PPI) network analysis were applied to investigate the function of DEGs. Nasal specimens from 90 CRSwNP and 45 controls were further collected and qRT-PCR was applied to verify the mRNA expression of hub genes, and moreover, their association with tissue eosinophilia and clinical characteristics in CRSwNP were analyzed.Results: Sixty-eight co-DEGs including 8 upregulated and 60 downregulated genes were identified and GO analyses identified the terms including positive regulation of ERK1 and ERK2 cascade, transforming growth factor beta receptor signaling pathway. PPI networks identified hub genes including EGF, ERBB4, AZGP1, CRISP3 and PIP which were validated to be significantly down-regulated in CRSwNP and showed well diagnostic prediction quality. In addition, lower mRNA expressions level of EGF and AZGP1 in eosinophilic CRSwNP compared with non-eosinophilic CRSwNP were found. Aberrant low expressions of EGF and AZGP1 protein in CRSwNP were identified, and there was good consistency between their mRNA expression level and protein relative expression level. Furthermore, the expressions of EGF and AZGP1 mRNA were significantly correlated with clinical severity parameters.Conclusion: Integrated analysis revealed 68 co-DEGs between nasal polyps and controls and identified hub genes, of which EGF and AZGP1 expression was significantly downregulated in eosinophilic CRSwNP and correlated with disease severity. Downregulation of EGF and AZGP1 may contribute to epithelial barrier dysfunction and type 2 inflammation in CRSwNP, suggesting them as potential diagnostic biomarkers and therapeutic targets.Keywords: chronic rhinosinusitis with nasal polyps, bioinformatics analysis, differentially expressed genes, EGF, AZGP1